Investigating the Role of Foreign Direct Investment on Economic Growth in Economic Sectors of Iran - adel mohammadinode; darush hasanvand; Hamid Asayesh (پژوهشهای اقتصادی, 2020)
The purpose of this paper is to estimate the direct effect of foreign investment on economic growth in agriculture, industry and services sectors in the provinces of Iran during the period 2001-2017. For this purpose, the Panel Smooth Transition Regression (PSTR) model used. It was found that there is a nonlinear relationship between foreign direct investment and the growth of various economic sectors. The results of this study indicate that foreign direct investment affects differently the growth of various economic sectors due to fluctuations in inflation rates. The estimated coefficients for the inflation rate threshold in three-menthioned sectors were 2.55, 1.78 and 1.94, respectively. In addition, one-percent increase in foreign direct investment would increase the growth rates of agriculture, industry, and service sectors by 0.50%, 0.69% and 0.88%, respectively.